Marine simulation and ship manoeuvrability : proceedings of the International Conference, MARSIM '96, Copenhagen, Denmark, 9-13 September 1996 /: proceedings of the International Conference, MARSIM '96, Copenhagen, Denmark, 9-13 September 1996. (2021) - Unknown
No abstract available